Opportunities for Improving Mechanisms of Sustainable Social Sphere Development of The Rural Areas of The Republic of Kazakhstan (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
The development of the socio-economic territories’ level is gradually decreasing. The young people flow from rural areas to large cities is increasing, social and household infrastructure is destroyed, ecological and demographic situations get worse. Rural workers’ wages are lower than in other industries. It is necessary to improve domestic and socio-economic conditions in rural areas so that to reform the decent living standard of country people.The rural areas’ social sphere needs to address the existing problems, related to life level and quality, the need to ensure a favorable social environment, especially in education and health care systems, vocational training, and the possibility of inclusion in the society labor potential.